Soft Skills Communication and Cognitive Development of First-Year Purposive Communication Students - GENESIS GREGORIOUS GENELZA (Program Studi Pendidikan Bahasa Inggris, ISDIK Kie Raha Maluku Utara, 2022)
The importance of a student's soft skills communication in language learning, particularly in their cognitive development, cannot be overstated. These skills, in turn, provide the groundwork for the development of other characteristics related to students' personal and career development. The descriptive correlational study aimed to verify the significant relationship between soft skills communication and cognitive development of the First-year Purposive Communication students. The findings revealed that there is a very high level of soft skills communication with a mean of 4.35. While cognitive development has a mean score of 4.44 which entails a very high distinction. On the other hand, when it comes to determining the significant relationship, it was found out that there is indeed a great connection between the two variables with a relationship value of 0.51 while its significance has a value of 0.0000000867. As a result, it is suggested that soft skills communication will have the same impact on students' cognitive development. The findings of this study show that each student's soft skills communication attribute is distinctive, and it can be improved by applying the lessons learned in ways that promote cognitive development, such as providing performance-based, outcomes-based, and other related and appropriate activities that require them to apply what they've learned. Further, based on the findings, it is recommended that this soft skills communication be extended and developed to other English subjects in the higher education curriculum, particularly the syllabus and assessment to use, in order to achieve higher cognition.